1966
DOI: 10.3181/00379727-122-31071
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on the Incubation of Tyrosine-UL-C14 with Beef Thyroid Tissue Slices.

Abstract: only ones through which feed-back control of immunoglobulin synthesis can operate. Therefore, under physiological conditions, the combined effect on regulation of antibody synthesis of all these structural features, might still be sufficiently specific without involving the antibody combining sites.Sunzmary. Regulation of immunoglobulin synthesis by feed-back inhibition was investigated so as to test whether the specificity of feed-back inhibition depends on recognition of allotypic specificities. This inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1973
1973
1973
1973

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…3c) is an indication of the normal metabo¬ lism of tyrosine by the thyroid gland. The suggestion by Dillard et al (1966) that the thyroid gland may show an abnormal tyrosine metabolism is unlikely in view of these experiments with mice in vivo (Text- fig. 1) and in vitro (Text- fig.…”
Section: Fraction Numbermentioning
confidence: 87%
See 1 more Smart Citation
“…3c) is an indication of the normal metabo¬ lism of tyrosine by the thyroid gland. The suggestion by Dillard et al (1966) that the thyroid gland may show an abnormal tyrosine metabolism is unlikely in view of these experiments with mice in vivo (Text- fig. 1) and in vitro (Text- fig.…”
Section: Fraction Numbermentioning
confidence: 87%
“…Their yields were low and Dillard, Hollingsworth & Bondy (1966) suggested that the thyroid gland may metabolize tyrosine abnormally. This suggestion was supported by the findings of Mosier (1966) who was unable to incorporate [14C]tyrosine into thyroglobulin although in his invitro system 131I incorporated into DIT and T4 was recovered from hydrolysed thyroglobulin.…”
Section: Introductionmentioning
confidence: 99%